COMMUNITY EMPOWERMENT THROUGH THE USE OF DRY COCONUT COIR INTO HANGING FLOWER POTS IN ULEE PULO VILLAGE DEWANTARA DISTRICT, ACEH UTARA DISTRICT - Nurmala; Jamilah; Sullaida; Cut Safani; Fatiya Azzahra (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2022)
The opportunity to develop coconut agribusiness into high economic value products is very large. The harvested coconut parts are copra, coconut cough and coconut husk. Dried coconut coir can be processed into hanging flower pots that can be sold at a price range of Rp. 15,000/unit up to Rp. 40,000/unit. The service activity aims to provide training on the use of dried coconut coir into hanging flower pots followed by 25 young women and housewives in Ulee Pulo Village, Dewantara District, North Aceh Regenc. In order to absorb information on the need and analysis of strategic conditions, activities were carried out using survey methods and focus group discussions (FGD) and demonstrations. Through this activity, it is hoped that it will open up business opportunities for hanging flower pot crafts in Ulee Pulo Village. The demonstration of making dried coconut coir is a form of skill for the community with an emphasis on artistic and innovative values so that the community is able to make flower pots from coconut coir with varied models and form small industrial groups in developing an independent business spirit. In this case, participants will be given training in the production management and marketing of competitive hanging flower pots. Through this activity, it is hoped that it will foster community participation, increase participants will be given training in the production management and marketing of competitive hanging flower pots. Through this activity, it is hoped that it will foster community participation, increase participants will be given training in the production management and marketing of competitive hanging flower pots. Through this activity, it is hoped that it will foster community participation, increase creativity, reduce unemployment and increase employment opportunities.